ROLE OF CALCIUM-REGULATING HORMONES, ADIPOCYTOKINES AND RENAL FUNCTION TEST IN THE PROGRESS OF TYPE 2 DIABETES MELLITUS IN A SAMPLE OF IRAQI PATIENTS - & Al-Lami, Al-Attaby (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
A cross-sectional study was conducted on 80 type 2 diabetic patients aged 20-60 years in Baghdad and 20 non diabetic persons as controls. Laboratory assessment of glucose related parameters; Fasting blood sugar (FBS), Glycated hemoglobin (HbA1c), Insulin and Insulin resistance (IR), renal function test; Blood urea, serum creatinine, Calcium (Ca) and Phosphorus (P), Calcium regulating hormones; Parathyroid hormone (PTH), calcitonin and vitamin D, cytokines, Adiponectin and Tumor necrosis factor (TNF-α) and comparison these parameters between patients and controls. The results: a high significant (p˂0.01) increase in FBG level in the patients (211.34 ± 11.20 mg/dl) as compared with control (85.89 ± 3.07 mg/dl). A high significant (p˂0.01) increase in HbA1c in the patients (8.89 ± 0.24 %) than to control (4.813 ± 0.09 %), insulin and HOMA2-I.R levels showed a high significant (P< 0.01) increase of patients as compared to control  (49.87 ± 15.78 vs. 12.16 ± 2.57 µIU/ml), (28.49 ± 10.77vs. 2.618 ± 0.56 µIU/ml)  respectively. A high significant (P